2021
DOI: 10.1017/s1368980021004511
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient comparisons of margarine/margarine-like products, butter blend products and butter in the US marketplace in 2020 post-FDA ban on partially hydrogenated oils

Abstract: Objective: To evaluate the fatty acid profiles and relevant vitamin and mineral compositions of margarine/margarine-like products and butter blend products available in the US marketplace and to compare with butter. Design: Analysis of the food and nutrient composition information available for margarine/margarine-like products, butter blend products and butter in the 2021 version of the University of Minnesota Nutrition Coordinating Center (NCC) Food and Nutrient Database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Besides vanaspati , other sources of TFAs, such as partially hydrogenated margarine and shortenings, are commonly used in street foods, such as roti canai , curry puff, chicken burgers, and donuts [ 36 ]. However, the findings in this study may suggest that the use of partially hydrogenated ingredients among vendors in Malaysia is low and that they might use tub-style margarine products which do not contain TFAs [ 42 ]. Notably, the substitution of stick margarine with tub margarine was found to be associated with a lower risk of CVD [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides vanaspati , other sources of TFAs, such as partially hydrogenated margarine and shortenings, are commonly used in street foods, such as roti canai , curry puff, chicken burgers, and donuts [ 36 ]. However, the findings in this study may suggest that the use of partially hydrogenated ingredients among vendors in Malaysia is low and that they might use tub-style margarine products which do not contain TFAs [ 42 ]. Notably, the substitution of stick margarine with tub margarine was found to be associated with a lower risk of CVD [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…ANOVA validated the reliability of the regression model, and it was found that the model could well predict the experimental results, as the p-value of the model was lower than 0.05 and the p-value for the lack of fit was higher than 0.05, with the predicted R 2 reasonably in agreement with the adjusted R 2 (variation within 0.2) . As presented in Table 3, all linear and quadratic coefficients had p-value lower than 0.05, indicating that they were all significant.…”
Section: Optimization Of Enzymatic Interesterification By Lipase Um1mentioning
confidence: 70%
“…The most common plastic fats in food industry were partial hydrogenated fat and naturally sourced plastic fat, like butter and some tropical plant sourced fat. The partial hydrogenation process (adding hydrogen to oils) allows for the creation of fats that are semisolid at room temperature from liquid oil 2) . However, epidemiological and clinical studies revealed that trans fatty acids produced from partial hydrogenation adversely affect human health, especially cardiovascular health 3) .…”
Section: Introductionmentioning
confidence: 99%
“… 28 Tough restrictions on food composition, such as banning artificial trans-fats from processed foods, may also prompt and accelerate replacement of those ingredients by healthier options. 29 Therefore, food reformulation strategies may be particularly suited to countries, such as China and the USA, where there was less support for governments to regulate food labelling and composition, perhaps due to concerns about the potential impact on the food industry, international trade and the economy. 30 …”
Section: Discussionmentioning
confidence: 99%